PENERAPAN MODEL PROBLEM BASED LEARING UNTUK MENINGKATKAN AKTIVITAS BELAJAR DAN HASIL BELAJAR IPAS MURID KELAS V SEKOLAH DASAR - Siti Mauliana; Dede Nuraida; Sri Rahayu Puji Lestari (STKIP Subang, 2026)
This classroom action research aimed to enhance the learning engagement and academic outcomes of fifth-grade students at UPT SD Negeri Kebonsari 3 in the Natural and Social Sciences (IPAS) subject by implementing the Problem-Based Learning (PBL) model. The study was motivated by low student engagement and IPAS learning outcomes that had not yet met the Learning Objective Mastery Criteria (KKTP). The research followed the Kemmis and McTaggart model and was conducted over two cycles, with each cycle comprising planning, implementation, observation, and reflection stages. The subjects were 21 fifth-grade students (11 boys and 10 girls) at UPT SD Negeri Kebonsari 3, Tuban. Data were collected through observation, written tests, and documentation, and subsequently analyzed descriptively. The results showed that student learning engagement increased from 45.23% (less active category) in the pre-cycle stage to 67.51% (good category) in Cycle I and 83.33% (very good category) in Cycle II. Class mastery of learning outcomes also improved from 28.57% in the pre-cycle stage to 52.38% in Cycle I and 80.95% in Cycle II, surpassing the success indicator of 75%. Thus, it can be concluded that the implementation of the Problem-Based Learning model is effective in enhancing learning engagement and IPAS learning outcomes for fifth-grade students.